NOTARY RESPONSIBILITIES ON THE MAKING OF DEED WITH DOUBLE NUMBER - I Wayan Erik Pratama Putra; Luh Putu Sudini; I Nyoman Alit Puspadma (NOTARIIL Jurnal Kenotariatan, 2020)
The objective of this research to reveal (1) the responsibility of a notary for the drafting of a double number and (2) the legal consequences if a double number occurs in a notarial deed. The types of this research is normative legal research. The research results indicated that (1) The notary's responsibility for making a notarial deed with a double number must be accounted for administratively. The existence of a double number on the notary deed indicates that the notary has been inadvertently applied in making an authentic deed. In every legal action that implies the use of authority, it implies an obligation of accountability. Thus, a notary who makes a notarial deed with a double number requires the notary to be administratively responsible, remembering that the negligence made by a notary is an administrative error; and (2) The legal consequences in the event of a double number in a notary deed do not cause any consequences if no party feels disadvantaged by the existence of this double number. All that is left is for the notary to publish the minutes of changing the deed number and notify parties such as the parties, the Ministry of Law and Human Rights and the local Land Office if the double-numbered deed is related to land rights. However, if the double numbered deed brings harm to another party, then the party who feels disadvantaged can sue the notary.